Interstate Assistance to the Use of Force - Nußberger, Benjamin K. (Kölner Schriften zum Friedenssicherungsrecht - Cologne Studies on International Peace and Security Law - Études colonaises sur le droit de la paix et de la sécurité internationale, 2023)
Whenever States use force in their international relations, interstate assistance is a vital component. The book clarifies the regulation of interstate assistance to a use of force under international law. It comprehensively reviews the relevant practice of States in United Nations resolutions, in international treaties and in more than 25 armed conflicts - from the Korean War to the current Ukraine war. It situates the regulation within the historic development of the ius contra bellum and contextualizes it with general rules of international law on complicity. Thereby, the book also sheds light on ambiguities of the regulation, thus providing the basis for more transparency and explicit discourse among both practitioners and scholars.